RASCH MODEL FOR GENDER-BASED ANALYSIS OF INNOVATION BEHAVIOR AMONG CULINARY MSME ENTREPRENEURS IN INDONESIA - Mardatillah, Annisa; Sari, Meci Nilam (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to accurately assess and analyze culinary MSME entrepreneurs' innovation behavior gender based and the differences between the instrument items. The instrument in this research was developed by examining the concepts and theories of innovation behavior and testing 109 entrepreneurs. Determining the sample size in this study used purposive sampling. Data analysis was carried out using the Rasch model. The findings of this research produce significant differences in the innovative behavior of business actors based on gender from the research instrument, which consists of 13 indicator items. Significant differences were found in items directly related to promoting idea concepts. Male entrepreneurs are likelier than women to agree with the idea implementation component. Regarding seeking support, women are more likely to agree than men. Male entrepreneurs like challenges more than women. This research contributes to developing the knowledge of business actors' innovation behavior, seen from their readiness to innovate based on gender to improve business performance. Furthermore, it guides the government in designing more inclusive innovation policies, training programs, and better support for MSME entrepreneurs.